2018
DOI: 10.1016/j.epsl.2018.06.038
|View full text |Cite
|
Sign up to set email alerts
|

The role of melt composition on aqueous fluid vs. silicate melt partitioning of bromine in magmas

Abstract: 25Volcanogenic halogens, in particular bromine, potentially play an important role in the ozone 26 depletion of the atmosphere. Understanding bromine behaviour in magmas is therefore crucial 27 to properly evaluate the contribution of volcanic eruptions to atmospheric chemistry and their 28 environmental impact. To date, bromine partitioning between silicate melts and the gas phase 29 is very poorly constrained, with the only relevant experimental studies limited to investigation 30 of synthetic melt with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 95 publications
8
44
2
Order By: Relevance
“…The challenge to interpreting BrO observations is highlighted by Cadoux et al (2018). GOME-2 observations of Merapi's eruption in Indonesia 2010 resulted in extremely low BrO/SO 2 ratios (maximum 8 × 10 −6 ; Hörmann et al, 2013), much lower than expected based on petrological estimates of the halogen/sulfur emission.…”
Section: Bro As a Fraction Of Total Bromine Under Different Plume Conmentioning
confidence: 99%
See 3 more Smart Citations
“…The challenge to interpreting BrO observations is highlighted by Cadoux et al (2018). GOME-2 observations of Merapi's eruption in Indonesia 2010 resulted in extremely low BrO/SO 2 ratios (maximum 8 × 10 −6 ; Hörmann et al, 2013), much lower than expected based on petrological estimates of the halogen/sulfur emission.…”
Section: Bro As a Fraction Of Total Bromine Under Different Plume Conmentioning
confidence: 99%
“…GOME-2 observations of Merapi's eruption in Indonesia 2010 resulted in extremely low BrO/SO 2 ratios (maximum 8 × 10 −6 ; Hörmann et al, 2013), much lower than expected based on petrological estimates of the halogen/sulfur emission. Cadoux et al (2018) discussed that BrO formation could be limited by the restriction of photochemical driven reactions caused by the ash-rich paroxysmal phase and the absence of UV light during the eruption in the night (the BrO was detected by GOME-2 in the following day). According to Cadoux et al (2018) other possibilities include: (a) scavenging of bromine in the troposphere (e.g., adsorption of bromine on ash), (b) kinetic factors lead to favored S degassing from the magma, (c) brine saturation leading to Br uptake when magma rises, and (d) changes in Br partitioning caused by other volatile species in the magma.…”
Section: Bro As a Fraction Of Total Bromine Under Different Plume Conmentioning
confidence: 99%
See 2 more Smart Citations
“…Halogen compounds, like chlorine and bromine, contributes to catalytic ozone depletion in the stratosphere (Brasseur and Solomon, 2005;Solomon, 1999). There is welldocumented petrological evidence that large to extremely large explosive volcanic eruptions emitted environmentally significant amounts of chlorine and bromine (Cadoux et al, 2015(Cadoux et al, , 2018Krüger et al, 2015;Kutterolf et al, 2013Kutterolf et al, , 2015Vidal et al, 2016). Furthermore, recent atmospheric observations revealed that even relatively small volcanic eruptions can inject significant amounts of halogen compounds in the stratosphere (for review and overview discussions see (von Glasow et al, 2009;Krüger et al, 2015;WMO, 2018).…”
Section: Introductionmentioning
confidence: 99%